Economic analysis of membrane-based separation of biocatalyst : mode of operation and stage configuration - Kapavarapu, Mohanish Sai Raghavendra Sridhar (Nanyang Technological University, 2022)
In the pharmaceutical industry, biocatalysts are mainly utilized for synthesizing Active Pharmaceutical Ingredients (API’s) and their intermediates. API purification is one of the vital steps in pharmaceutical downstream processing as the product purity affects the market value of the drug. Membrane separation is a cost-effective and sustainable separation process mainly preferred due to its lower energy consumption. However, there is not any specific analysis that deals with the economics of a membrane separation unit specific to biocatalyst separation in pharmaceutical industry. So, this study presents insights into the economics of an ultrafiltration (UF) unit for various operating modes and stage configurations in biocatalyst separation. It was estimated from the current study that a capital expenditure of $1.35 million and an annual operating expenditure of $85 thousand are required to set up a new UF unit to obtain 640 million litres of permeate annually for input of 100,000 L/hr of feed. The cost components of the UF unit at constant flux mode, constant transmembrane pressure (TMP) mode and four different stage configurations were assessed. The analysis on the mode of operation to obtain the desired recovery of 80% suggests operating the unit at a constant flux mode (capital of $1.35 million and annual operating cost of $85.60 thousand at 55 LMH) rather than constant TMP (capital of $2.34 million and annual operating cost of $124.25 thousand at 0.25 MPa) mode due to higher area requirement and annual membrane replacement costs in the latter case. The analysis of the stage configuration shows the variation of cost expenditures with additional stages to improve recovery and purity. When compared to the single-stage configuration, the costs nearly doubled (capital of $2.82 million and annual operating cost of $145.77 thousand) in the three-stage configuration to operate the unit with the highest purity and recovery. This study can be used to understand the variations in expenditure to choose the right operating values and make decisions during industrial design and planning.